2008
DOI: 10.1590/s0102-86502008000100004
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and functional evaluation of distal esophagus of rabbits submitted to esophageal infusion with caustic soda

Abstract: The ingestion of caustic substances is an important emergency situation, because of its serious consequences. Purpose: To study morphological and functional alterations of the esophagus in rabbits submitted to esophageal infusion of caustic soda (NaOH). Methods: The 88 rabbits studied were divided into 4 groups: G 1 (n=22) were submitted to esophageal infusion with distilled water. G 2 , G 3 , and G 4 were submitted to esophageal infusion of 2%, 4% and 6% NaOH respectively. Morphological alterations were studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Our observations also indicate that the vagally stimulated LES relaxation is mediated through axial stretch on the LES exerted by the longitudinal muscle contraction of the esophagus. (6), rabbit (19,22), and opossum (12,17)] to study the LES. For several reasons, opossum has been used most extensively because the LES and distal esophagus in the opossums, similar to humans, consist of smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Our observations also indicate that the vagally stimulated LES relaxation is mediated through axial stretch on the LES exerted by the longitudinal muscle contraction of the esophagus. (6), rabbit (19,22), and opossum (12,17)] to study the LES. For several reasons, opossum has been used most extensively because the LES and distal esophagus in the opossums, similar to humans, consist of smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Bakan et al [13] have reported tissue damage in the rat esophageal samples that have gradually increased at 4, 24, 48, and 72 h after application of 10% NaOH. In another experimental study performed in rabbits, it has been demonstrated that esophageal infusion with 6% NaOH caused intense and diffuse lesions, with ulcers and large areas of necrosis, more serious at 6 and 24 h after infusion [14].…”
Section: Discussionmentioning
confidence: 97%
“…La sévérité des lésions produites par les substances caustiques sur le tissu dépend du type, de la quantité et de la concentration de la substance caustique ingérée [3][4][5][6][7][8] aussi bien que de la période du contact avec la muqueuse [3][4][5][6]. L'endoscopie digestive haute est le principal examen morphologique initial [9,10].…”
Section: Mots Clés Produit Caustique · Ingestion · Endoscopieunclassified